2013
DOI: 10.1017/s1368980013002310
|View full text |Cite
|
Sign up to set email alerts
|

Disadvantaged pre-schoolers attending day care in Salvador, Northeast Brazil have a low prevalence of anaemia and micronutrient deficiencies

Abstract: Objective: To examine the micronutrient status of disadvantaged pre-schoolers from Northeast Brazil, following the introduction of pro-poor policies, by assessing the prevalence of anaemia and micronutrient deficiencies and the role of sociodemographic factors, genetic Hb disorders and parasitic infections. Design: In a cross-sectional study, data on sociodemographic status, health, growth, genetic Hb disorders, parasites and nutrient supply from day-care meals were obtained. Fasting blood samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Lander et al noted a modest association between serum zinc and anemia in preschool children. 20 They studied serum selenium, ferritin, transferrin receptor, folate, VB12 and a-thalassemia, and found that serum selenium, retinol and hemoglobinopathy predicted Hb level, but that iron status markers such as ferritin and transferrin receptor did not. In contrast, the present case-control study assessed Asian children with age and racial differences, and analyzed the differences in zinc level according to anemia status.…”
Section: Discussionmentioning
confidence: 99%
“…Lander et al noted a modest association between serum zinc and anemia in preschool children. 20 They studied serum selenium, ferritin, transferrin receptor, folate, VB12 and a-thalassemia, and found that serum selenium, retinol and hemoglobinopathy predicted Hb level, but that iron status markers such as ferritin and transferrin receptor did not. In contrast, the present case-control study assessed Asian children with age and racial differences, and analyzed the differences in zinc level according to anemia status.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the recruitment of the preschoolers, their socio-demographic, anthropometric, micronutrient, and infection status have been reported earlier [ 16 , 17 ]. Briefly, a cross-sectional study of 376 disadvantaged preschoolers aged between 3 and 6 years was conducted in seven philanthropic daycare centers located in Salvador, the capital city of Bahia, NE Brazil from August – November, 2010.…”
Section: Methodsmentioning
confidence: 99%
“…A faecal concentrate was examined by microscopy for the presence of helminths and hookworm, whereas data on the treatment for de-worming in the last 6 months was obtained by mother or caregiver report via questionnaire [ 16 ]. Morning fasting veni-puncture blood samples were drawn for analyses of haemoglobin (Hb), serum zinc and selenium, as described in detail earlier [ 17 ]. Briefly, serum zinc was analyzed by flame atomic absorption spectrophotometry (ContrAA 700, Analytik Jena, Germany) and serum selenium by electrothermal atomic absorption spectrophotometry (AA-800, Perkin Elmer 2690, Ebos Group Ltd, Auckland, New Zealand).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations